2007
DOI: 10.1596/1813-9450-4424
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nutritional Status Through Behavioral Change : Lessons From Madagascar

Abstract: This paper provides evidence of the effects of a largescale intervention that focuses on the quality of nutritional and child care inputs during the early stages of life. The empirical strategy uses a combination of double-difference and weighting estimators in a longitudinal survey to address the purposive placement of participating communities and estimate the effect of the availability of the program at the community level on nutritional outcomes. The authors find that the program helped 0-5 year old childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 38 publications
2
24
2
Order By: Relevance
“…Paternal nutritional status is both less studied and less strongly predictive of malnutrition in international literature [17]; its importance in determining stunting may be a unique feature of our study, which included a large set of matched fathers, or of this population. This contrasts with previous studies in Madagascar which have attributed malnutrition to behavioral factors, poor maternal education, and male sex [25,2729], and to international literature emphasizing parental education and behaviors [13,19] and male sex [13,17,21] as risk factors for malnutrition. The lack of association with vaccination and supplementation in our study provides evidence that these factors, which may mediate the relationships between parental education, work, and nutrition [18,20], are less important in this population.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Paternal nutritional status is both less studied and less strongly predictive of malnutrition in international literature [17]; its importance in determining stunting may be a unique feature of our study, which included a large set of matched fathers, or of this population. This contrasts with previous studies in Madagascar which have attributed malnutrition to behavioral factors, poor maternal education, and male sex [25,2729], and to international literature emphasizing parental education and behaviors [13,19] and male sex [13,17,21] as risk factors for malnutrition. The lack of association with vaccination and supplementation in our study provides evidence that these factors, which may mediate the relationships between parental education, work, and nutrition [18,20], are less important in this population.…”
Section: Discussioncontrasting
confidence: 91%
“…Environmental factors such as rural location predispose to malnutrition in this population, similar to international ones [13,17]. Interventions to address malnutrition in Madagascar, which have focused on parental education and supplemental feeding [26,27,30], may need to be augmented with earlier, household-level, and population-level interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, although maternal education targeted towards improving child-care practices has not always been effective on its own (19) , a study in Madagascar showed that it can be effective where participatory approaches are used, networks of women's groups are supportive and the quality of the child-care services delivered is improved by training local community nutrition workers (20) . But the pathways that can translate maternal education into improved child nutrition need to be further clarified.…”
Section: Evidence For the Effectiveness Of Indirect Interventionsmentioning
confidence: 99%
“…On conditional cash transfers: Attanasio et al (2005); on community nutrition programs: White and Masset (2007); Hossain et al (2005); Galasso and Umapathi (2009) ;Galasso, Umapathi, and Yau (2011);Alderman et al (2009); on early child development programs: Armecin et al (2006); Alderman (2007); Alderman et al (2006);Behrman, Cheng, and Todd (2004).…”
Section: Introductionmentioning
confidence: 99%